Analisis Manajemen Persediaan Bahan Baku Dengan Metode Economic Order Quantity (EOQ) Pada UMKM Osha Snack - Alsa Az Zukhruf; Elfa Syukrina; Diyah Puspa Asih Atsilanti; Abib Riyadi; Luthfi Hibatullah; Agung Prayudha Hidayat; Astiani Safitri (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This research was conducted to determine the economic quantity of raw material inventory and determine the amount of raw material inventory needed. This research is included in descriptive quantitative research using the Economic Order Quantity (EOQ) method. EOQ can achieve optimal inventory levels and overall cost reductions, thereby enabling businesses to achieve maximum profits. The subject of this research is the raw material inventory of Osha Snack Bogor. In using this EOQ technique, it can be concluded that cooking oil is the largest raw material inventory, which is 32.40% of the total inventory with an EOQ amount of 8485 liters. The next order of cooking oil should Osha Snack do when the inventory in the warehouse remains 38 liters.